Detection of impaired glucidic metabolism and insulin resistance in a pilot child sample - Mauro-Martin, Ismael San; López-Oliva, Sara; Garicano-Vilar, Elena; García-de Angulo, Belén; Blumenfeld-Olivares, Javier Andrés (Universidad y Salud, 2019)
Introduction: Metabolomics enables the study of insulin resistance (IR), a risk factor for pre-diabetes and diabetes. Quantose IRTM is the only test that measures IR using the euglycemic hyperinsulinemic clamp. Objective: The effectiveness of a metabolomic test for the detection of RI markers in a child population was verified. Materials and methods: Eleven children aged 8.54 ± 3.53 years with diabetes risk factors were recruited from the El Escorial Hospital. The American Diabetes Association (ADA) Standards (5,7-6,4% HbA1C and 100-125 mg/dl basal glucose) were established as diagnostic criteria for prediabetes. Blood tests were compared to the Quantose IRTM assay studying the metabolomic profile related to IR (alpha-hydroxybutyric acid, oleic acid, linoleo-glycerophosphocoline and insulin). This analysis generated a Quantose© score of IR > 63. Results: None of the subjects met the ADA criteria for prediabetes: HbA1C=5,3±0,18 and glucose=86,6± 5,6 mg/dl. On the contrary, 10 subjects met the Quantose IRTM test criterion for IR (score: 78,09 ± 9,24 (>63)). Conclusions: The Quantose IRTM test measures the percentage of glucose bound hemoglobin within red blood cells. This assay makes it possible to predict diabetes risk and take preventive measures.